Cloning and expression of NS2B/NS3 protein of DENV3 Indonesia strain in Saccharomyces cerevisiae expression system for the development of Dengue vaccine - ASRI SULFIANTI; SABAR PAMBUDI; ISMA NUR AZIZAH; DODDY IRAWAN SETYO UTOMO; ABINAWANTO ABINAWANTO (Microbiology Indonesia, 2018)
NS3 protein is 618 amino acids (aa) in length containing serine protease and helicase domains required for DENV replication. Alignment of consensus amino acid sequences from all four DENV serotypes demonstrated that this protein is more conserved (78%) among the different dengue serotypes, which elicits a strong cellular immune response after viral infection in humans and animal models. Present study, a central hydrophilic region of NS3 cofactor, NS2B (NS2BH) with full length of NS3 genes DENV3 Indonesian strain were amplified from CDNA following PCR, and inserted to PYES2/CT shuttle vector. The recombinant plasmid was transformed and expressed in Saccharomyces cerevisiae expression system. As result, detection with Anti-His detector and Anti-NS3 shown NS2BH/NS3 was expressed as 83 KDA protein band. We found that addition of NS2BH on NS3 full length construction plasmid increase the yield and activity of protein expression in S. cerevisiae. In future study, our recombinant NS2B/NS3 protein can be used as recombinant protein in Dengue vaccine development.